Online customer reviews as a powerful marketing tool / Baderisang Mohamed and Nor Fitrah Anaik Ali - Mohamed, Baderisang; Anaik Ali, Nor Fitrah (Faculty of Business & Management, Universiti Teknologi MARA (UiTM) Cawangan Kedah, 2021)
Social media are becoming a more popular option for companies and brands to market their product and services as it is proven by previous research that marketing is more effective on these platforms, especially if the product is segmented towards the youngsters. Besides the hard work brands pull off to market their products, reviews from consumers are considered a huge success factor in online marketing. This article aims to analyze various aspects on how online customer reviews contributes as a powerful marketing tool and influence purchase decision.